2020
DOI: 10.1111/mve.12452
|View full text |Cite
|
Sign up to set email alerts
|

Preferential attraction of different colours of light emitting diodes for Culicoides species in West Bengal, India

Abstract: The preferential attraction of adult Culicoides (Diptera: Ceratopogonidae) to specific wavelengths was studied in West Bengal, India. A total of 280 collections were made with suction light traps fitted with various colours of light emitting diodes (LEDs) placed at cattle sheds during June, August and November in 2017. In addition, the numbers that have been collected in the evening and morning were compared. Locally manufactured suction light traps fitted with ultra violet (UV), blue, green, yellow, pink, red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, the similar species composition, physiological age were present in UVLT collection. Mazumdar and Mazumdar (2020) theorized that these two species exhibited a higher attractiveness towards UVLT than other species. Considering all species, an overall higher percentage may be due to the presence of large numbers of blood-engorged specimens C. peregrinus and/or C. fulvus in sites: S4, S5, S6, S7, S9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the similar species composition, physiological age were present in UVLT collection. Mazumdar and Mazumdar (2020) theorized that these two species exhibited a higher attractiveness towards UVLT than other species. Considering all species, an overall higher percentage may be due to the presence of large numbers of blood-engorged specimens C. peregrinus and/or C. fulvus in sites: S4, S5, S6, S7, S9.…”
Section: Discussionmentioning
confidence: 99%
“…Light trap collection data fail to predict the exact biting and attack rate of midges, but a higher percentage of freshly blood fed individuals of C. peregrinus and C. fulvus , both of which are potential vectors of BTV, were present in UVLT collection. Mazumdar and Mazumdar (2020) theorized that these two species exhibited a higher attractiveness towards UVLT than other species. Considering all species, an overall higher percentage may be due to the presence of large numbers of blood‐engorged specimens C. peregrinus and/or C. fulvus in sites: S4, S5, S6, S7, S9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This species is thought to have the potential for the spread of African horse sickness virus (AHSV) along with Culicoides imicola Kieffer, 1913, principal vector of AHSV (Bakhoum et al, 2016; Dennis et al, 2019; Fall et al, 2015). Various studies reported C. oxystoma as one of the predominant species in Indian backyard farms (Harrup et al, 2016; Harsha et al, 2020; Kar, Mondal, Ghosh, et al, 2022; Kar, Mondal, Pal, et al, 2022; Mazumdar & Mazumdar, 2020) and to be abundant in BT‐infected areas (Chanda et al, 2019). Kar, Mondal, Ghosh, et al (2022) also reported large numbers of C. oxystoma attacking cattle and sheep in open pastures and it preferred cattle over sheep and goat.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the brightness of the light source may influence the efficiency of the trap for some species of mosquitoes (Barr et al ., 1960). Although several studies have dealt with the evaluation of the effectiveness of different wavelength of light (Bishop et al ., 2004, 2006; Hope et al ., 2015; Silva et al ., 2015; González et al ., 2016; Harrup et al ., 2016; Venter et al ., 2018; Mazumdar & Mazumdar, 2020) for the attraction of Culicoides , studies regarding the brightness of the light are limited. Light intensity was shown to play a significant role in increasing the numbers of especially Cuicoides brevitarsis Kieffer collected with green LEDs in Australia (Bishop et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%